Collective autonomy in the European Union: theoretical, comparative and cross-border perspectives on the legal regulations of collective bargaining - Iossa, Andrea (Lund, 2017)
"‘Collective Autonomy in the European Union’ explores the question of collective autonomy by investigating the relationship between collective bargaining and legal regulation and its current evolution in the national contexts and in the EU internal market. The thesis aims at achieving a comprehensive understanding of the notion, function and exercise of collective autonomy and collective bargaining, and it argues that collective autonomy and collective bargaining in contemporary Europe present challenges that alter their basic features. To this end, the thesis undertakes a multifaceted analysis integrating three perspectives: a theoretical perspective analysing and combining the conceptual elements of collective autonomy and collective bargaining as defined in industrial relations theories, labour law theories, and in the discourses on global labour rights; a comparative perspective analysing how collective autonomy and collective bargaining have found legal regulation in the Italian and Swedish labour law and industrial relations contexts; a cross-border perspective examining how the EU regulation of the internal market freedoms of establishment and to provide services impacts on the features of collective autonomy and collective bargaining. By combining elements of international, European and comparative labour law, EU internal market law, and industrial relations, this thesis explores the unique features of collective autonomy and collective bargaining as socio-economic mechanisms having a normative power, whose functioning is however influenced by legal dynamics. Eventually, it examines the transformation that the foundations of collective autonomy and collective bargaining undergo in relation to the challenges deriving from both the processes of company-level decentralisation and the dynamics of the cross-border scenarios in the EU internal market. Ultimately, the thesis contributes to advancing the understanding of the foundations of collective autonomy and to exploring its operations beyond national borders."